Hermeneutic Shakespeare (Taylor & Francis, 2023)
Shakespeare, Literary Theory, Literature and Philosophy
English
Keywords: Shakespeare, Literary Theory, Literature and Philosophy; thema EDItEUR::D Biography, Literature and Literary studies::D Biography, Literature and Literary studies::DS Literature: history and criticism